A Descriptive Study on the Factors Affecting the Length of Stay in the Emergency Department of a Tertiary Private Hospital in the Philippines - Jimenez, Ma. Lourdes D (Archīum Ateneo, 2018)
Objective. The study aims to describe factors that contribute to the Length of Stay (LOS) in the Emergency Department (ED) patients of a Tertiary Private Hospital in Philippines. Methods. This is a retrospective descriptive study from September 1, 2015 to March 31, 2016 on the factors of ED consultations specifically on demographics (age and sex), payment schemes (Out of Pocket (OOP) and third party payer), shift times (morning, afternoon and night) and triage-levels were associated with LOS. Results.Our ED consultations with age (mean 40.75 years, SD 16.8, N 20,687, range 95) were dominated by females (56%), two age-range, 21-30 (28.4%) & 31-40 and third party payer (57%). LOS (mean of 4,40 hours, SD 3,89, N 18540, range 68) was significantly higher (p Conclusion. Higher LOS was associated on the following: urgent and emergent triage- levels, older age range, OOP, and morning and afternoon shifts.